Morphological diagnosis and successful treatment of chorioptic mange in 2 South American coatis (Nasua nasua) - Klinger, Christoph J.; Boehm, Teresa M.S.A.; Roller, Marco; Knauf-Witzens, Tobias (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2021)
Two female South American coatis (Nasua nasua) kept in a zoo in Southern Germany presented with pruritus and moderate hair loss at the dorsal trunk, thigh areas and alongside the tail. Otherwise the animals showed no clinical signs. While the clinical general examination as well as cytology of dermatologic samples showed no pathologic changes, Chorioptes sp. mites could be identified in a superficial skin scraping. Two consecutive topical applications of a selamectin/sarolaner spot-on formulation 4 weeks apart lead to a complete resolution. No side effects were observed.
Keywords: Chorioptes sp.; psoroptidae; procyonidae; topical therapy; selamectin; sarolaner